The Impact of Digital Transformation on the Business Sustainability of MSMEs in Denpasar City - Pertiwi, Inten; Puspa, Gede; Prasiani, Ni Komang; Sihwinarti, Dwi (Dinasti Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy; however, they face significant challenges in sustaining their businesses in the digital era. This study aims to analyze the impact of digital technology adoption and digital skills on the business sustainability of MSMEs in Denpasar City. A quantitative descriptive approach was employed, utilizing primary data collected through questionnaires from 100 respondents. The findings indicate that both digital technology adoption and digital skills have a positive and significant influence on MSME business sustainability. The implementation of digital technology has been proven to enhance operational efficiency, expand market reach, and strengthen competitiveness. However, challenges such as limited digital literacy, financial constraints, and uneven technological infrastructure remain significant obstacles. This study concludes that digital transformation, supported by well-planned strategies and stakeholder collaboration, can drive the sustainability of MSMEs in Denpasar City.